PENGALAMAN KARIES GIGI MOLAR PERTAMA PERMANEN BERDASARKAN RIWAYAT PENDIDIKAN TAMAN KANAK-KANAK: CARIES EXPERIENCE OF PERMANENT FIRST MOLAR TOOTH BASED ON THE PRE- ELEMENTARY EDUCATIONAL BACKGROUND - Ristya Widi Endah Yani; Windhy Putri Utami (Dentika: Dental Journal, 2011)
Children in pre-educational ages are vulnerable to the caries of the permanent first molar. Early prevention on this problem may be conducted through promotion of oral and dental health to pre-educational children such as in the education of kindergarten. The aim of this study was to observe the diff erence of the number of caries in the permanent first molar in children of 7-8 years old with pre- elementary and non pre- elementary educational backgrounds. The study was an observational study with cross-sectional approach. The population was elementary school students of 7- 8 years old at Patrang District Jember Regency. The samples were obtained using stratified random sampling. Total sample was 314 students, consit of 157 pre-elementary (kindergarten) and 157 non pre- elementary. Data was analyzed using MannWhitey Test. The result showed that caries without experience of permanent first molar in the children of 7- 8 years old with was 0.07 pre-elementary and 0.44 pre- elementary. It can be concluded that there was a significant differencebetween caries experience of the permanent first molar in the children aged 7-8 years old with and without pre-elementary educational backgrounds .